Lactococcus lactis FNBPA+ (pValac:e6ag85a) Induces Cellular and Humoral Immune Responses After Oral Immunization of Mice - de Castro, Camila Prósperi; Souza, Bianca Mendes; Mancha-Agresti, Pamela; Pereira, Vanessa Bastos; Zurita-Turk, Meritxell; Preisser, Tatiane Melo; da Cunha, Vanessa Pecini; dos Santos, Janete Soares Coelho; Leclercq, Sophie Yvette; Azevedo, Vasco; Miyoshi, Anderson (Frontiers in Microbiology, 2021)
The development of a new vaccine strategy against tuberculosis is urgently needed and has been greatly encouraged by the scientific community worldwide. In this work, we constructed a lactococcal DNA vaccine based on the fusion of two Mycobacterium tuberculosis antigens, ESAT-6 and Ag85A, and examined its immunogenicity. The coding sequences of the ESAT-6 and Ag85A genes were fused and cloned into the eukaryotic expression pValac vector, and the functionality of the vector was confirmed in vitro. Then, L. lactis FnBPA+ (pValac:e6ag85a) was obtained and used for oral immunization of mice. This strain induced significant increases in IFN-γ, TNF-α and IL-17 cytokines in stimulated splenocyte cultures, and significant production of antigen-specific sIgA was observed in the colonic tissues of immunized mice. We demonstrated that L. lactis FnBPA+ (pValac:e6ag85a) generated a cellular and humoral immune response after oral immunization of mice. The strategy developed in this work may represent an interesting DNA mucosal vaccine candidate against tuberculosis, using the fusion of two highly immunogenic antigens delivered by safe lactic acid bacteria.